The future of interactive literature - Tiippana, Timo (My University, 2022)
Interactive literature is a fresh form of literature that has not yet existed even for a hundred years, yet it has a wide history, jumping between continents and including a number of evolutionary steps. Its evolution is still ongoing and this thesis aims to map out where it might be headed next. The first part of the thesis focuses on unearthing the past of interactive literature in full, starting all the way from the first gamebook released in 1930 and making its way to the present. The second part builds on this by trying to see where it might be heading next. For this purpose a scenario-based questionnaire (focusing on technological advancements) was deployed on forums filled with both consumers and developers of interactive literature. Answers to the questionnaire ended up being quite few and biased towards developers so the results are analyzed with a grain of salt. Also past personal experience in writing interactive literature is discussed in order to provide a more writer-centric perspective into currently available tools and needs.

Interaktiivinen kirjallisuus on tuore kirjallisuuden muoto, joka ei ole edes sata vuotta vielä, mutta sen historia on kattava, hyppien mantereelta toiselle lukuisien evoluution muotojen myötä. Tämä evoluutio on vieläkin menossa ja tämä tutkielma pyrkii selvittämään minkä muodon se ottaa seuraavaksi. Tutkielman ensimmäinen osa keskittyy interaktiivisen kirjallisuuden historian kokonaisvaltaiseen selvittämiseen. Tutkimus alkaa ensimmäisestä pelikirjasta, joka julkaistiin vuonna 1930 jatkaen siitä aina nykypäivään asti. Tutkielman toinen osa rakentaa edellisen päälle yrittäen selvittää mikä olisi seuraava askel historiassa. Tämän selvittämiseksi tutkielma käyttää skenaariopohjaista kyselyä, jota esitettiin erilaisilla foorumeilla, joiden käyttäjiin kuului niin interaktiivisen kirjallisuuden kuluttajia kuin kehittäjiäkin. Kyselyyn saatiin vain muutamia vastauksia jotka tulivat suurimmaksi osaksi kehittäjiltä, joten tulokset analysoidaan tämä huomioon ottaen. Kyselyn lisäksi myös kertynyttä henkilökohtaista kokemusta interaktiivisen kirjallisuuden kirjoittamisesta käydään läpi. Tämä tuo kirjoittaja läheisemmän näkökulman tarjolla oleviin työkaluihin ja tarpeisiin.
Keywords: interactive literature, visual novel, text-adventure, hyperfiction, gamebook, interactive fiction